The effect of biomechanical and viscoelastic properties of gastrocnemius (lateral-medial) muscle and achilles tendon on jumping performance in professional soccer players - Seyhan, S. (International Journal of Disabilities Sports and Health Sciences, 2024)
Anaerobic performance (vertical jumps) is an important indicator in determining athletic performance in soccer. The aim of this study was to investigate the effects of biomechanical and viscoelastic properties of lateral and medial gastrocnemius (LG&MG) muscle and achilles tendon (AT) on jumping performance of professional soccer players. A total of 21 male professional soccer players with a mean age of 18.19±0.40 years, a mean height of 180.48±6.25 cm, a mean body weight of 70.71±7.82 kg, and a mean BMI of 21.66±1.65 kg/m2 were included in this study. LG and MG muscle, as well as AT biomechanical and viscoelastic properties were evaluated with Myoton Pro device. Measurements were performed in the prone position of the soccer players, LG and MG at 50° plantar flexion, and AT at 0° (neutral position) at an angle of 4 cm above the calcaneal tubercle. Counter movement jump (CMJ) were recorded with the high-speed camera in the validated My Jump 2 application. A significant correlation was observed between the LG (F) tension value and CMJ (P) value and between the MG (R&C) values and the CMJ (F&P) value of professional soccer players (p<0.05). There was no significant relationship between AT values and CMJ values (p>0.05). It should not be forgotten that training coaches on this subject and applying this information to soccer players by conscious coaches will bring about increases in the athletic performance of soccer players, and all these performance characteristics can be achieved with planned and programmed training.